Mindsets and mirrors: How growth mindsets shape anthropomorphism in AI‐enabled technologies - Chen, Qian Qian; Yi, Youjae (Psychology & marketing, 2024)
Across multiple studies, we found that people with a growth mindset (whose abilities are believed to be developable) are more likely to see artificial intelligence (AI) devices as human‐like. This effect holds for intelligent personal assistants, where growth‐mindset users attributed more human qualities to these AI helpers. Furthermore, people with a growth mindset were more open to new experiences and felt less threatened by AI, which in turn made them see AI as more human‐like. Interestingly, the more human‐like the AI features became, the less a growth mindset influenced how human‐like people perceived the AI. Our findings highlight the importance of designing AI that can be personalized and adapt to user needs. They also suggest a connection between how human‐like AI appears and how threatening people perceive it. This knowledge can be used to create AI technology that is user‐centered and fosters positive interactions.